Making public service motivation count for increasing organizational fit : the role of followership behavior and leader support as a causal mechanism - Jin, Myung H. (2020)
Many studies in public administration have modeled employees’ person–organization fit perceptions as a function of public service motivation, but previous work has not adequately addressed the causal relationship between these concepts. This article represents the first attempt to explain the “black box” that links public service motivation to person–organization fit. Given the various positive benefits associated with person–organization fit in the literature, an understanding of the mechanisms that underpin its relationship with public service motivation has important managerial implications for leaders regarding their interactions with individual employees. Extending the work-based affect model designed by Yu, we explore how PSM increases person–organization fit perceptions through employee followership and leader support as a potential causal chain. The results from a survey of 692 faculty members at a public university are consistent with the predicted three-path mediation model. Among these respondents, higher levels of public service motivation were associated with greater followership behavior, which, in turn, increased positive perceptions of person–organization fit through greater leader support.